Employment and Welfare Effects of Short-Time Work in Germany - Kilian Niedermayer; Jan Tilly (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We study the employment and welfare effects of short-time work in Germany during the recession between 2008 and 2010. Using a unique matched employer-employee data set that contains the universe of workers and employers for the metropolitan area of Nuremberg, we document the intensive and extensive margin of short-time work. We then develop and estimate an equilibrium search model in which worker-firm matches are subject to productivity shocks that differ in expected duration. After observing the realization of productivity, a worker-firm match decides whether to work full-time, lay off the worker, or use short-time work. Employed workers accumulate human capital whereas unemployed workers' human capital depreciates. Laid off workers can be recalled by their previous employers. We find that for every four workers on short-time work, one job was saved during the recession.
Keywords: J64; J08; J38; 330